IMPLEMENTASI SISTEM PRODUKSI SECARA ISLAMI PADA PRODUK HASIL PENGOLAHAN IKAN (STUDI KASUS DI UMKM UPI MINO NGUDI LESTARI YOGYAKARTA) - Oktarina, Amimah; Asnaini, Anaini (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2016)
In producing the goods when viewed from the perspective of the Islamic way of production, manufacturers produce the goods in an attempt to create maslahah, which seek profit through production that is not prohibited and protected from the exploitation of natural resources. Maslahah itself is divided into two components, namely the benefits and blessings. Production activities can be seen in the development of Micro, Small and Medium Enterprises (SMEs) is currently one example of the active role of government in promoting the productivity of the people in the industry. Pembangungan industry effort aimed at expanding employment opportunities and increase production. One form of community contributions by active production activities are SMEs Fish Processing Unit (UPI) Mino Ngudi Lestari, located in the hamlet of Nayan, Maguwoharjo, Yogyakarta. The main problem is formulated in this research is how the production of products of fish processing in Mino UPI Ngudi Lestari viewed from the perspective of production in Islam. The results of this research are production systems that are applied by SMEs UPI Mino Ngudi Lestari manage fish into refined products overall compliance with production systems in Islamic. Of the several factors highlighted, all these factors have been in accordance with the production system Islamically, just revamping the organizational factors that need to be better.Keywords: Islamic Production, Products, Fish, SMEs